The Association Between College Students` Participation Behavior and Social Media Use - Kilinc, Emin; Tarman, Bulent; Yussupova, Saule (Research in Social Sciences and Technology, 2023)
This paper examines college students` participation behaviors and the use of social media tools. The descriptive survey model was applied to investigate university students` participation behaviors. The data was collected through a “Participation Questionnaire” from 284 college students in Kazakhstan. The result showed that students who spend less time on social media are positively related to participatory citizenship. Moreover, students with fewer social media accounts are more likely to engage in political, volunteer, and social events than students with more social media accounts.